Long non-coding RNA XIST negatively regulates thoracic aortic aneurysm cell proliferation by targeting the miR-193a-5p/KLF7 axis: Negative Regulation of Thoracic Aortic Aneurysm Cell by XIST - Zhu, Ming; Tan, Mengwei; Xu, Fazhen; Huang, Yuting; Yang, Jiantian (Cellular and Molecular Biology, 2022)
Non-coding RNAs (ncRNAs) are important molecular modulators in diverse pathological processes, influencing the occurrence and progression of carcinomas. Thoracic aortic aneurysm (TAA) is an infrequent disease among aneurysmal diseases and accounts for nearly 3% of diagnosed aneurysms. The functional roles of long ncRNA (lncRNA) XIST and miR-193a-5p and the associated molecular mechanisms are yet to be investigated. In the current study, we discovered that miR-193a-5p was expressed at low levels in the blood of TAA patients. Further, loss-of-function and gain-of-function assays disclosed that miR-195-3p impacted the proliferation ability of TAA cells. XIST was found to be the most overexpressed lncRNA among predicted lncRNAs binding to miR-193a-5p. The promotive function of XIST in TAA was also explored. Subsequently, KLF7 was proved to be the downstream factor of the XIST/miR-193a-5p axis. Rescue assays testified the whole regulation mechanism of the XIST/miR-193a-5p/KLF7 axis in TAA. MiR-193a-5p was absorbed by XIST for the improvement of KLF7 in TAA. These results concluded that XIST might be engaged in TAA pathogenesis via regulation of the miR-193a-5p/KLF7 axis, supplementing more therapeutic options for TAA treatment.